Leptospirillum: a study of the nitrogen fixing capabilities - Corbett, Melissa Kaye (Curtin University, 2011)
This project sought to determine the response of Leptospirillum species subject to conditions without soluble nitrogen. The most significant outcome of this work was the identification of the nifHDK genes in L. ferriphilum and observations of its continued ability to survive in environments without soluble nitrogen. The sustained proliferation of all three Leptospirillum species studied, combined with the structural analysis of these genes, provides evidence of functional nitrogen fixation in each of these species.